Clinical and angiographic outcomes following endovascular treatment of very small (3 mm or smaller) intracranial aneurysm: A single-center experience. Issue 37 (September 2017) - Liu, Yongsheng; Wang, Feng; Fu, Xiaochen; Liu, Yongjian; Zhang, Guodong; Xu, Ke
Abstract : Abstract: Treatments for very small (3 mm or smaller) intracranial aneurysms (VSAs) remain controversial. The aim of this study was to evaluate the efficacy of endovascular treatment for VSAs and to evaluate clinical risk factors associated with complications. This retrospective study enrolled 82 VSA patients who underwent coil embolization in our institution. Angiographic outcomes were assessed according to the Meyers classification. The clinical results were evaluated using the modified Rankin scale (mRS) immediately after coiling, at discharge, and during follow-up. A Mann-Whitney U test was performed for non-normally distributed continuous variables. A Pearson χ 2 test or Fisher's exact test was performed for categorical variables. Among 82 aneurysms, 54 were treated with stent-assisted coiling (SAC) embolization. Thromboembolic complications were seen in 2 patients (2.4%). Intraoperative rupture occurred in 4 patients (4.9%). Other adverse events occurred in 2 patients (2.4%). Two patients (2.4%) had permanent disabling neurologic deficit (mRS 3–6) because of complications. The overall mortality rate was 1.2%. Adverse events were correlated with the location of aneurysms ( P  = .02), Fisher grade ( P  = .01), and treatment experience ( P  = .03). Patients with middle cerebral artery (MCA) bifurcation and anterior communicating artery (ACoA) aneurysms were more likely to experience a higher incidence of complication. Thirty-five patients underwent angiographic follow-up. The complete occlusion rate improved from an immediate 37.8% to 80.0% at follow-up. In the short term, coiling is a safe and effective approach for the treatment of VSAs. SAC may be associated with a high rate of further occlusion during short-term follow-up. Endovascular treatment of VSAs at middle cerebral artery bifurcation or anterior communicating artery is associated with a higher incidence of complications.